APPROCHE HYDROGEOCHIMIQUE A L’ETUDE DE LA FLUORATION DES EAUX DE LA NAPPE DU COMPLEXE TERMINAL DE LA BASSE VALLEE DE L’OUED M’YA (OUARGLA) Hydrogeochemical approach to study the water fluoridation of the Terminal Complex aquifer in the low algeria - NEZLI, Imed Eddine; ACHOUR, Samia; HAMDI-AÏSSA, Baelhadj (Courrier du Savoir, 2014)
Le présent travail porte sur la présence et l’origine géochimique du fluor dans les eaux de la nappe du Complexe Terminal (CT) de Ouargla. Les résultats obtenus montrent qu’il existe avec des teneurs variables allant de 0,9 à 1,42 mg.l -1 . Le calcul de l’indice de saturation des eaux par les minéraux dominants ,en utilisant le modèle thermodynamique Phreeqci, révèle la susceptibilité des minéraux carbonatés à la précipitation, et les minéraux évaporitiques et fluorurés à la dissolution.   The present work deals with the presence and the hydrochemical origin of fluoride in Terminal Complex aquifer of Ouargla. The results show the presence of fluoride in studied water. The concentrations vary between 0,9 and 1,42 mgl -1 . The calculation of water saturation index in relation to the preponderant minerals, using the thermodynamic model phreeqci reveals a sensitivity of carbonate minerals towards precipitation, and dissolution of evaporitic minerals and fluorides clays as well.